P3_4 Honey, I Shrunk the Tank! - Harding, Ben; Kneebone, Ricky; Acton, Jack; Harvey, Max (Physics Special Topics, 2017)
In the 2015 film "Ant-Man", a Russian T-34 tank is shrunk down to the size of a keychain, during which its mass remains constant. By estimating the change in inter-atomic spacing, and the resulting increase in Coulomb repulsion between atomic nuclei, the energy required for this compression is found to be approximately 7.08x10^15 J. This an extremely large amount of energy, making the possibility of such a situation infeasible.